GRANTSISM: An Excel™ ice sheet model for use in introductory Earth science courses. Issue 2 (3rd April 2018) - Kirchner, Nina; van Dongen, Eef; Gowan, Evan J.; Pattyn, Frank; Noormets, Riko; Jakobsson, Martin; Ingólfsson, Ólafur
ABSTRACT: GRANTISM (GReenland and ANTarctic Ice Sheet Model) is an educational Excel™ model introduced by Pattyn (2006). Here, GRANTISM is amended to simulate the Svalbard-Barents-Sea Ice Sheet during the Last Glacial Maximum, an analogue for the contemporary West Antarctic Ice Sheet. A new name, "GRANTSISM, " is suggested; the added S represents Svalbard. GRANTSISM introduces students of bachelor's or master's programs in Earth sciences (first or second cycle program in the Bologna system for higher education), but with little or no background in numerical modeling, to basic ice sheet modeling. GRANTSISM provides hands-on learning experiences related to ice sheet dynamics in response to climate forcing, and fosters understanding of processes and feedbacks. GRANTSISM was successfully used in noncompulsory courses in which students have been able to reproduce paleo-ice sheet evolution scenarios discussed here as examples. Students progressed further by designing, developing, and analyzing their own modeling scenarios. Here, we describe GRANTSISM and report on how learning activities with GRANTSISM were assessed by students who had no prior experience in ice sheet modeling. The response rate for a noncompulsory survey of the learning activity was less than 40%. A subsequent control experiment with a compulsory survey, however, showed the same patterns of answers, so the student response is considered representative. First, GRANTSISM is concluded to be a highly attractive tool to introduce learners with an interest in ice sheet behavior to ice sheet modeling . Second, it triggers an interest for more in-depth learning experiences related to numerical ice sheet modeling.